Grazing exclusion increases soil organic C through microbial necromass of root-derived C as traced by 13C labelling photosynthate - Qu, Qing; Deng, Lei; Gunina, Anna; Hai, Xuying; Deng, Jun; Shangguan, Zhouping; Kuzyakov, Yakov (Biology and fertility of soils, 2024)
Grasslands store large amounts of C; however, the underlying mechanisms of soil C sequestration after grazing exclusion are not well known. This study aimed to elucidate the drivers of soil organic C (SOC) sequestration from plant and microbial residues in temperate grasslands after long-term (~ 40 years) grazing exclusion. We conducted in situ 13 C-CO 2 labelling experiments in the field and traced 13 C in plant-soil systems paired with biomarkers to assess the C input from plants into soils. Long-term grazing exclusion increased all plant and soil pools including shoots, roots, microbial biomass and necromass. 13 C allocation in these pools also increased, whereas 13 C was lost via respiration as CO 2 from soils decreased. 13 C incorporation into the soil and microbial biomass increased with 13 C allocation into the roots. Grazing exclusion for over 40 years increased the total SOC content by 190%, largely due to increases in fungal necromass C, and there was a minor contribution of lignin phenols to SOC accrual (0.8%). Consequently, grazing exclusion boosts not only aboveground biomass, but also larger roots and rhizodeposition, leading to microbial biomass and necromass formation. Microbial necromass and lignin phenols contribute to SOC accrual under grazing exclusion, and microbial necromass, especially fungal necromass, makes a larger contribution than lignin phenols.